From sugar binders to diabetes fighters: the lectin saga of antihyperglycemic activity through systematic review and meta-analysis - Simha N., Akshaya; Patil, Shashank M.; M. K., Jayanthi; N., Chaitra; Wong, Ling Shing; Kijsomporn, Jureerat; Raj, Ranjith; Ramu, Ramith (Frontiers in Pharmacology, 2024)
Introduction Lectins are carbohydrate-binding proteins that are extremely selective for sugar groups in the other molecules. As a result, they perform a variety of roles in biological processes involving cell, carbohydrate, and protein recognition at the cellular and molecular levels. Because lectins can bind to carbohydrates, they may play a role in determining the rate of carbohydrate digestion. They also bind to some proteins involved in diabetes mellitus (DM) pathophysiology. The present review aims to summarize the efficiency of lectins from different sources as potential antihyperglycemic agents. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were employed for the drafting. In this regard, published scientific articles on the effects of different lectins on blood glucose (BG), glucose tolerance, hormonal effects, carbohydrate-digesting enzymes, oxidative stress, and insulin production process were collected from reputed journals using electronic databases. Furthermore, the toxicity effects of lectins from different sources were collected. A specific keyword search was completed to collect numerous articles with unique experimental designs and significant results. This was followed by the selection of the requisite articles based on the criteria designed by the authors. Data extraction was based on the common research elements included in the articles. Results and Discussion Of 13 identified studies, 11 studies were considered after double screening based on the inclusion criteria. All 11 pharmacological investigations were considered for review. Subsequent studies reflected on the pharmacological properties of lectins on the levels of BG, oxidative stress, β-cell proliferation, insulin resistance, inhibition of carbohydrate digesting enzymes, body weight, food and water intake, lipid profile, and other parameters. This review highlights lectins as potential anti-diabetic agents. Conclusion However, due to limited research, systematic evaluation is recommended for their development and promotion as effective potential antihyperglycemic agents. The clinical efficacy and safety of lectins against diabetes mellitus must also be evaluated.